Analisis Perbandingan Risiko Nilai Tukar Kurs Dinar (Emas), Dolar AS, Euro dan Yuan (Periode 2010 – 2015) - Andi Triyawan; Atina Rohmah (Institut Agama Islam Negeri Madura, 2017)
Money is a tool intermediary humans to perform the transaction payment is national or international. In its development money undergoes several changes. Similarly, in the development of the world economy, there has been a financial crisis that hit in various countries, such as the global economic crisis. Crisis economic global is the crisis that occurred as a result of the problems of economic markets in the whole world who make entire sectors of the economy markets experienced a collapse and the impact on other sectors . Which becomes a problem in terms of this is the risk of the value of the exchange currency money and the occurrence of fluctuations in the value of exchange currency money internationally which led to a decrease in the value of the exchange currency for money in countries developing. That is, because the use of fiat money system based only on the belief of its value without any intrinsic value in fiat money form . The purpose of this research is to know how big is the risk of the value of exchange and volatility that is generated in the use of value exchange currency currency exchange rate of Dinar ( Gold ), Dollars USA, Euro and Yuan as the eyes of money internationally. This research is a study of Library Research with quantitative research type, by obtaining secondary data from site Internet. By taking samples as much as 60 months of each exchange Dinar Gold, Dollars USA, Euro and Yuan by way of purposive sampling and using the Analysis Time Series with Eviews 7.2. The results of the research of this is that the volatility of the value of the exchange currency for money top is Dinar Emas with value of 0.036590, while the volatility of most small is the value of the exchange currency Yuan with a value of 0.018472. Dinar Gold has a value of volatility and risk value of the exchange of the most high , so that when the dinar gold is used in terms of trade internationally and the company would have borne the risk of market which is bigger than use with US Dollars, and more. Suggestions of researchers is hopefully the research further more better and get the data the price of the commodity of gold that is more clear and accurate between the value of the price of gold that with the availability of a form of gold.